HUBUNGAN KEJENUHAN KERJA (BURNOUT) DENGAN KEPUASAN KERJA PUSTAKAWAN DIREKTORAT PERPUSTAKAAN UNIVERSITAS ISLAM INDONESIA - Joko Sugeng Prianto; Arif Cahyo Bachtiar (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
This study aims to determine whether there is work burnout felt by librarians at the Library Directorate of the Islamic University of Indonesia (UII). If the results of this study show symptoms of work burnout, it will be measured to what extent the work saturation is. Then, this research will also show a picture of job satisfaction of the librarians of the Directorate of Library UII. This research uses a quantitative approach with descriptive methods. This research is a population study that will make all librarians at the Directorate of Library UII as research subjects. The results showed that the average score of work saturation (burnout) based on the MBI for librarians in the Directorate of Library UII was 5.15. The average score of job satisfaction experienced by librarians in the UII Library Directorate is 30.48. There is a relationship between job burnout (burnout) and librarian job satisfaction in the Directorate of Library UII which shows a value of -0.489. This means that in this study the librarian burnout level was rather low followed by job satisfaction which was at the level of satisfaction.